An Analysis of Parents’ Support on Students’ English Achievment During Covid 19 Outbreak - Mayang Sari, Ayu; Riswanto; Serasi, Reko (JPT : Jurnal Pendidikan Tematik, 2022)
The aim of this study are: 1) To identify the kinds of parents’ support on students’ English learning process during Covid-19 outbreak, 2) To know the parents support contributes to the improvement of the students’ English achievement during Covid-19 outbreak. This study was conducted in descriptive qualitative research. Interview was used to obtain the data. Both the data was analyzed inductively based on Creswell (2008). The result of this study showed that: 1) The supports given by the parents are motivation support; facilitate support and the material support in this Covid-19 outbreak, and 2) The students have good English skill because their own motivation and supported by their parents.